Primary Virus-Cell Interactions in the Immuno-fluorescence Assay of Venezuelan Equine Encephalomyelitis Virus - Hahon, Nicholas (1967)
The conditions under which Venezuelan equine encephalomyelitis (VEE) virus attached to host cells markedly influenced the assay of virus by the fluorescent cell-counting technique. When virus inoculum was centrifuged onto McCoy cell monolayers, approximately 97% of virus was attached to cells within 10 min, in contrast to 34% after stationary incubation at 35 C for 2 hr. Maximal binding of virus occurred only in the presence of 0.1 to 0.15 m NaCl. This salt requirement, added to evidence of (p)H dependence and temperature independence of VEE virus attachment to cells, indicated that the initial union involved electrostatic forces. Virus penetration, measured by the insensitivity of virus-cell complexes to viral antiserum, was complete in 30 min at 35 C. The process was temperature-dependent and un-affected by the ionic content of medium. For assay of VEE virus by the fluorescent cell-counting technique, infected cells may be enumerated as early as 12 hr after infection of cell monolayers. The relationship between virus concentration and cell-infecting units was linear; the distribution of fluorescent cells was random. The virus assay was equivalent in sensitivity but more precise and rapid than that of intracerebral inoculation of mice.